Large diameter fully covered self‐expanding metal stent placement for palliation of proximal malignant esophageal strictures. Issue 6 (15th May 2014) - Bassi, M.; Luigiano, C.; Fabbri, C.; Ferrara, F.; Ghersi, S.; Alibrandi, A.; Fuccio, L.; Virgilio, C.; Patelli, M.; Zanello, M.; Cennamo, V.
Summary In patients with malignant esophageal strictures within 6 cm from the upper esophageal sphincter, self‐expanding metal stents placement represents a challenge because there is an increased risk of complications. The aim of this study was to assess the safety and effectiveness of large‐diameter WallFlex® fully covered self‐expanding metal stents for palliation of patients with proximal malignant esophageal strictures. From March 2010 to December 2012, 12 patients with proximal strictures (4–6 cm from the upper esophageal sphincter) and six with very proximal strictures (<4 cm from the upper esophageal sphincter) were palliated with this fully covered self‐expanding metal stent and included in the study. Technical success was 100% and clinical success was 94%. The mean baseline dysphagia score was 3.2, and 1 week after stenting it improved significantly to 1.3 (P < 0.001). Early complications occurred in four patients, more frequently in patients with very proximal strictures as compared with patients with proximal strictures (P = 0.02). Late complications occurred in five patients, and there were no differences between patients with very proximal strictures or proximal strictures (P = 0.245). The mean survival after stent placement was 119 days, and no differences between patients with very proximal strictures versus proximal strictures were found (P = 0.851). There was no stent‐related mortality or 30‐day mortality. Our results suggested that a large‐diameter fully covered self‐expanding metal stent is an effective and secure device for palliation of patients with proximal malignant esophageal strictures.